Simultaneous maximum power tracking of wind turbine and diesel engine for optimal power extraction of a small-scale hybrid wind-diesel system - Virata, Adrian Jay A. (College of Engineering, University of the Philippines Diliman, 2015)
The integration of wind energy conversion system (WECS) to existing diesel generator system is an imeediate step for developing a highly sustainable practical system that offers minimal pollution. It was already established that maximizing extracted power from the wind reduces the amount of energy needed from the diesel generator. However, integrating WECS tends to increase the variability of operation of the diesel system due to the intermittent nature of the wind. In addition, low load operation times also increase making the diesel engine operate inefficiently for longer hours. In this study, a hybrid wind-diesel system is devised so that simultaneous optimal power extraction from wind and fuel source can be obtained. A maximum power point tracker was designed to extract power from the wind turbine optimally and the diesel enginer was made to operate at variable speed for least fuel consumption. A comparison is made between the performance of a conventional fixed speed diesel enginer hybrid system and the devised system.